2018
DOI: 10.3389/fneur.2018.00509
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Myoclonic Epilepsy Shows Potential Structural White Matter Abnormalities: A TBSS Study

Abstract: Background: Several studies on patients with juvenile myoclonic epilepsy (JME) showed widespread white matter (WM) abnormalities in the brain. The aim of this study was to investigate potential structural abnormalities in JME patients (1) compared to healthy controls, (2) among JME subgroups with or without photoparoxysmal responses (PPR), and (3) in correlation with clinical variables.Methods: A selection of 31 patients with JME (12 PPR positive) and 27 age and gender matched healthy controls (HC) were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…At present, some studies on frontal lobe focal motor epilepsy have shown that the FA and MD values of the bilateral suboccipital frontal tract, bilateral anterior thalamus radiation, bilateral corticospinal tract, and bilateral inferior fronto-occipital fasciculus have abnormal changes [ 36 ]. In our study, the abnormalities in the ipsi-tumoral cingulum and uncinate fasciculus fiber tracts were consistent with the former report, except for the frontal part of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, some studies on frontal lobe focal motor epilepsy have shown that the FA and MD values of the bilateral suboccipital frontal tract, bilateral anterior thalamus radiation, bilateral corticospinal tract, and bilateral inferior fronto-occipital fasciculus have abnormal changes [ 36 ]. In our study, the abnormalities in the ipsi-tumoral cingulum and uncinate fasciculus fiber tracts were consistent with the former report, except for the frontal part of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the abnormalities in the ipsi-tumoral cingulum and uncinate fasciculus fiber tracts were consistent with the former report, except for the frontal part of the corpus callosum. Since the increase in the MD value of the fiber tracts indicates the destruction of the sphingomyelin layer or a decrease in the axon density [ 36 , 37 ], the MD indicates the viscosity of the fluid and is sensitive to white matter edema or damage [ 38 ]. It is known that such damage to the white matter skeleton plays an important role in the occurrence of epilepsy [ 39 , 40 , 41 , 42 ]; therefore, we consider that the occurrence of frontal lobe epilepsy related to glioma might be associated with damage to the fiber tracts above.…”
Section: Discussionmentioning
confidence: 99%
“…181 Another study compared 31 patients with JME (12 PPR positive) and 27 healthy controls matched for age/sex also using TBSS. 182 These authors showed reduced FA in longitudinal fasciculus, inferior fronto-occipital fasciculus, corticospinal tract, anterior and posterior thalamic radiation, corona radiata, corpus callosum, cingulate gyrus, and external capsule. However, subgroup analysis revealed no significant differences of white matter alterations between PPR positive and negative patients and with clinical and epilepsy-related factors.…”
Section: Brain Imaging and Photosensitivitymentioning
confidence: 94%
“…Yet another study conducted tract‐based spatial statistics (TBSS) analysis in 8 patients with photosensitive epilepsy (PSE) and 16 age‐/sex‐matched healthy individuals; PSE participants had significantly lower FA values in the corpus callosum 181 . Another study compared 31 patients with JME (12 PPR positive) and 27 healthy controls matched for age/sex also using TBSS 182 . These authors showed reduced FA in longitudinal fasciculus, inferior fronto‐occipital fasciculus, corticospinal tract, anterior and posterior thalamic radiation, corona radiata, corpus callosum, cingulate gyrus, and external capsule.…”
Section: Photic Eeg and Imagingmentioning
confidence: 99%
“…More than a dozen publications evaluated WM integrity and orientation in JME brains using diffusion tensor imaging (DTI) (Deppe et al, 2008; Keller et al, 2011; Liu et al, 2011; Vulliemoz et al, 2011; Kim et al, 2012, 2015; O’Muircheartaigh et al, 2012, 2011; Focke et al, 2014; Ekmekci et al, 2016; Gong et al, 2017; Domin et al, 2018). All of these publications reported decrease in fractional anisotropy (FA), a measure reflecting the microstructural integrity of various WM tracts.…”
Section: Neuroimaging Analysis and Neuropathologymentioning
confidence: 99%